Multi-Objective Parameter Optimized Design of Self-Oscillating Cavitation Jet Nozzles - Tengwei Wang; Guohui Li; Mengbin Song; Yuanyuan Zhao; Wei Xu; Fujian Zhao; Xiuli Wang (Energies, 2023)
Self-oscillating cavitation jet technology has become a research hotspot of scholars in various fields. However, existing research lacks a summary of the rules of the influence of various factors on the cavitation performance, such that efficient and stable extensive engineering applications are impossible to achieve. This paper aims at optimizing the design of the self-oscillating cavitation jet nozzle (SOCJN) as the objective; this is carried out by the experimental design, optimal Latin hypercube method, and response surface method in (design of experiment) DOE methods on the basis of the ISIGHT optimization method. In addition, taking the vapor volume fraction and cavitation number as a research objective, the obtained optimal structural parameters of the nozzles are applied under the condition of clear water to establish the function mapping relationship between the external geometric characteristics and the vapor volume fraction and cavitation number; then, this is compared with the experiment. The results indicate that the second-order response surface approximate model is suitable for the SOCJN and there is an error smaller than 8% between the approximate model results and the calculated results of the nozzle response. When the diameter of the upper nozzle is D1 = 4.7 mm, the ratio of the upper nozzle’s diameter to the lower’s diameter (D1/D2) is 2.6 and the ratio of the chamber length to the chamber diameter (L/D) is 0.63; pulse jets from the SOCJN have the best pitting effect on the sample at the monitoring point when the convergence angle of collision wall α is 120°. When the structural parameters of the nozzle are optimal structural parameters, the cavitation performance is the best at the initial pressure of 4.8 MPa. This research provides a reference for the optimized design of the SOCJN for industrial applications.